2001
DOI: 10.1098/rspb.2000.1394
|View full text |Cite
|
Sign up to set email alerts
|

Detection of palm fruit lipids in archaeological pottery from Qasr Ibrim, Egyptian Nubia

Abstract: In modern times, the trees of the palm family have been of great economic and social importance to the people in Egypt, as in other parts of the world. There are various species of palm and although di¡erent parts of the tree can be used, the fruit are of great value. In antiquity, it is expected that the palm fruit would also have been of great importance to people in the region. The chemical analysis of absorbed residues in archaeological pottery is well established, and through the investigation of ceramic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…Furthermore, it has been shown that this level of preservation is also mirrored at the molecular level in archaeological plant remains (e.g. [22,52]) and lipids in pottery vessels [7][8][9].…”
Section: Qasr Ibrimmentioning
confidence: 99%
“…Furthermore, it has been shown that this level of preservation is also mirrored at the molecular level in archaeological plant remains (e.g. [22,52]) and lipids in pottery vessels [7][8][9].…”
Section: Qasr Ibrimmentioning
confidence: 99%
“…[3,10,12]). Although degradation occurs during burial, appreciable amounts of lipid can survive over archaeological time periods.…”
Section: Introductionmentioning
confidence: 97%
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%